Mechanisms of resistance to tyrosine kinase inhibitor‐targeted therapy and overcoming strategies - Ou, Xuejin; Gao, Ge; Habaz, Inbar A.; Wang, Yongsheng (MedComm (2020), 2024)
Tyrosine kinase inhibitor (TKI)‐targeted therapy has revolutionized cancer treatment by selectively blocking specific signaling pathways crucial for tumor growth, offering improved outcomes with fewer side effects compared with conventional chemotherapy. However, despite their initial effectiveness, resistance to TKIs remains a significant challenge in clinical practice. Understanding the mechanisms underlying TKI resistance is paramount for improving patient outcomes and developing more effective treatment strategies. In this review, we explored various mechanisms contributing to TKI resistance, including on‐target mechanisms and off‐target mechanisms, as well as changes in the tumor histology and tumor microenvironment (intrinsic mechanisms). Additionally, we summarized current therapeutic approaches aiming at circumventing TKI resistance, including the development of next‐generation TKIs and combination therapies. We also discussed emerging strategies such as the use of dual‐targeted antibodies and PROteolysis Targeting Chimeras. Furthermore, we explored future directions in TKI‐targeted therapy, including the methods for detecting and monitoring drug resistance during treatment, identification of novel targets, exploration of dual‐acting kinase inhibitors, application of nanotechnologies in targeted therapy, and so on. Overall, this review provides a comprehensive overview of the challenges and opportunities in TKI‐targeted therapy, aiming to advance our understanding of resistance mechanisms and guide the development of more effective therapeutic approaches in cancer treatment.